Transport of cytoskeletal elements in the squid giant axon. - Terasaki, M (1995)
In order to explore how cytoskeletal proteins are moved by axonal transport, we injected fluorescent microtubules and actin filaments as well as exogenous particulates into squid giant axons and observed their movements by confocal microscopy. The squid giant axon is large enough to allow even cytoskeletal assemblies to be injected without damaging the axon or its transport mechanisms. Negatively charged, 10- to 500-nm beads and large dextrans moved down the axon, whereas small (70 kDa) dextrans diffused in all directions and 1000-nm beads did not move. Only particles with negative charge were transported. Microtubules and actin filaments, which have net negative charges, made saltatory movements down the axon, resulting in a net rate approximating that previously shown for slow transport of cytoskeletal elements. The present observations suggest that particle size and charge determine which materials are transported down the axon.